What Happens after Assignments? The Room for Manoeuvre of Committee Members in the Bundestag and the Tweede Kamer. Issue 2 (22nd February 2018) - Mickler, Tim A
Abstract: This article analyses how parliamentary party groups in the Tweede Kamer and the Bundestag achieve internal cohesion via the working procedures of parliamentary committees. Earlier research has indicated that committees comprise legislators with more or less divergent views from the parliamentary party group (PPG) median. This begs the question what mechanisms exist to deal with internal conflicts and maintain a level of cohesiveness among committee members and the wider PPG. The analysis is based on evidence from interviews with 78 legislators. The results show how individual legislators develop the initial positions with relative autonomy but are subsequently placed in a system of scrutiny through the internal working groups established in the PPGs. The analysis also highlights informal relationships between legislators outside of the institutionalised patterns.